The Effect of Lavender Aromatherapy in Reducing Emesis Gravidarum (First Trimester) - Bella Puspa Sari; Yuniarti Yuniarti; Kosma Heryati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Pregnancy is an event that occurs in a woman. Some uncomfortable things will come along with the physiological changes during pregnancy such as nausea, vomiting, and frequent urination. The most uncomfortable is nausea and vomiting (emesis gravidarum). Nausea and vomiting (emesis gravidarum) during pregnancy are common symptoms and often occur in the first trimester of pregnancy. One treatment to reduce non-pharmacological therapy is giving lavender aromatherapy. The purpose of this study was to determine the effect of lavender aromatherapy in reducing emesis gravidarum in the Telaga Dewa Public Health Center, Bengkulu City in 2021. The type of research used in this research is pre-experiment with One Group Pre-Test Post-Test design. The sampling technique in this study was using purposive sampling technique with a total sample size of 38 respondents and data collection using the PUQE-24 checklist sheet. The analysis method uses the Wilcoxon and Chi-Square test. The results of the Wilxocon test showed that there was an effect of giving lavender aromatherapy in reducing emesis gravidarum (p-value = 0.000). The results of the Chi-Square test showed that only one external variable had a relationship with the incidence of emesis gravidarum in first trimester pregnant women, namely parity obtained (p-value = 0.010). It is expected that pregnant women in the first trimester can apply lavender aromatherapy as an alternative to non-pharmacological therapy to overcome emesis gravidarum in first trimester pregnant women.